2014
DOI: 10.1007/s13202-014-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of ionic liquids for chemical enhanced oil recovery

Abstract: Substantial amount of crude oil remains in the reservoir after primary and secondary production. Chemical flooding is one of the enhanced oil recovery (EOR) methods; however, chemicals (i.e., Surfactant) used are sensitive to the harsh environment characterizing the local reservoirs. The current study aimed at investigating the utilization of ionic liquids (ILs), known as environment friendly salt with good solubility, thermal stability and effective surface activity, as an alternative to conventional organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…5, and the particles that have high SSA providing an excess pressure in the wedge/film. Buckley and Fan (2005) suggested that the hydrophilic silica nanofluids can give a high performance on oil recovery because of wettability alteration and the reduction on the IFT. The IFT influences capillary pressure, capillary number, and adhesion tension.…”
Section: Resultsmentioning
confidence: 99%
“…5, and the particles that have high SSA providing an excess pressure in the wedge/film. Buckley and Fan (2005) suggested that the hydrophilic silica nanofluids can give a high performance on oil recovery because of wettability alteration and the reduction on the IFT. The IFT influences capillary pressure, capillary number, and adhesion tension.…”
Section: Resultsmentioning
confidence: 99%
“…Bin‐Dahbag et al also mention that increasing the concentration of an IL (Ammoeng 102) resulted in decreasing the contact angle of the oil droplet, and caused a change in rock wettability from marginally oil‐wet to medium water‐wet conditions. Wettability alteration might therefore be the third possible mechanism contributing to the efficiency of [EMIM][Ac] in the recovery of oil, as observed by Bin‐Dahbag et al In summary, three possible mechanisms seem to be significant in improving the RF of oil using ILs, namely: electrostatic interactions, aromatic interactions, and viscous forces. As for the third mechanism, ILs with high viscosity cause an increase in the viscosity of the aqueous phase, leading to a decrease in mobility ratio between the aqueous and oil phases.…”
Section: Results Of Sandpack Flooding Testmentioning
confidence: 91%
“…Limited studies have been carried out to demonstrate the effects of wettability alteration by ionic liquids. Bin-Dahbag et al (2014) have done a series of flooding experiments on Berea sandstone samples by using different ionic liquids concentrations to investigate the wettability alteration [12]. It was concluded that ILs have the ability to shift the rock wettability from oil wet towards water wet as a result of the interaction between oil, rock, and IL [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bin-Dahbag et al (2014) have done a series of flooding experiments on Berea sandstone samples by using different ionic liquids concentrations to investigate the wettability alteration [12]. It was concluded that ILs have the ability to shift the rock wettability from oil wet towards water wet as a result of the interaction between oil, rock, and IL [12]. A similar study was conducted by Mohammed and Babadagli (2016) to investigate the effect of several imidazolium ionic liquids to modify the wettability of oil-wet limestone and sandstone.…”
Section: Introductionmentioning
confidence: 99%